Targeted therapy in gastroesophageal cancers: past, present and future - Woo, Janghee (Gastroenterol Rep (Oxf), 2015)
Gastroesophageal cancer is a significant global problem that frequently presents at an incurable stage and has very poor survival with standard chemotherapy approaches. This review will examine the epidemiology and molecular biology of gastroesophageal cancer and will focus on the key deregulated signaling pathways that have been targeted in the clinic. A comprehensive overview of clinical data highlighting successes and failures with targeted agents will be presented. Most notably, HER2-targeted therapy with the monoclonal antibody trastuzumab has proven beneficial in first-line therapy and has been incorporated into standard practice. Targeting the VEGF pathway has also proven beneficial, and the VEGFR-targeted monoclonal antibody ramucirumab is now approved for second-line therapy. In contrast to these positive results, agents targeting the EGFR and MET pathways have been evaluated extensively in gastroesophageal cancer but have repeatedly failed to show benefit. An increased understanding of the molecular predictors of response to targeted therapies is sorely needed. In the future, improved molecular pathology approaches should subdivide this heterogeneous disease entity to allow individualization of cancer therapy based on integrated and global identification of deregulated signaling pathways. Better patient selection, rational combinations of targeted therapies and incorporation of emerging immunotherapeutic approaches should further improve the treatment of this deadly disease.